2015
DOI: 10.1007/s00134-015-3849-3
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in vasopressin?

Abstract: Vasopressin in septic shockSeptic shock is associated with a relative deficiency of the endogenous stress hormone vasopressin. In shock states vasopressin binds to vasopressin receptors on vascular smooth muscle, producing intense vasoconstriction with minimal osmotic effects and resulting in increased blood pressure. Two recent meta-analyses report relative risks (RR) of short-term mortality in favour of vasopressin analogues compared to noradrenaline; however, using different methodologies, one group found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…The other potentially important finding from VASST that informed this trial was the potential interaction with corticosteroids. There are several possible biological interactions including that vasopressin binds to V1b receptors in the anterior pituitary that then leads to adrenocorticotropin hormone release 19 and corticosteroids have been shown to restore cytokine-mediated down-regulation of vasopressin receptors. 20 Patients in VASST who received vasopressin and corticosteroids had reduced mortality rates compared with patients who received norepinephrine and corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The other potentially important finding from VASST that informed this trial was the potential interaction with corticosteroids. There are several possible biological interactions including that vasopressin binds to V1b receptors in the anterior pituitary that then leads to adrenocorticotropin hormone release 19 and corticosteroids have been shown to restore cytokine-mediated down-regulation of vasopressin receptors. 20 Patients in VASST who received vasopressin and corticosteroids had reduced mortality rates compared with patients who received norepinephrine and corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…2 Centre for Heart Lung Innovation, St. Paul's Hospital, University of British Columbia, Vancouver, BC, Canada. 3 Centre for Perioperative and Critical Care Research, Imperial College Healthcare NHS Trust, London, UK. 4…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In shock states vasopressin acts as a potent vasoconstrictor via V1a receptors on vascular smooth muscle [3]. A relative deficiency of vasopressin in septic shock has been described [4] and administration of exogenous vasopressin reduces catecholamine requirements with the hypothesis that it may therefore also diminish the likelihood of catecholamine-related side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it appears to prevent microvascular leak and associated positive fluid balance in ovine models of sepsis [45,46]. For these reasons, selepressin may be preferable to vasopressin in septic shock [47]. In experimental studies, selepressin has been shown to more efficiently increase and stabilise mean arterial pressure, at lower doses than vasopressin [48], and to increase survival rates [49].…”
Section: Selepressinmentioning
confidence: 99%